2012
DOI: 10.1038/ncomms1706
|View full text |Cite
|
Sign up to set email alerts
|

The GOLD domain-containing protein TMED7 inhibits TLR4 signalling from the endosome upon LPS stimulation

Abstract: Toll-like receptor 4 is an innate immune receptor responsible for the recognition of the Gram-negative cell wall component lipopolysaccharide. Here we show that transmembrane emp24 domain-containing protein 7 (TmED7) inhibits myD88-independent toll-like receptor 4 signalling. TmED7 overexpression inhibits the ability of TRAm, an adaptor utilized by tolllike receptor 4, or lipopolysaccharide to activate the interferon regulatory factor 3-signalling pathway, whereas TmED7 knockdown enhances production of the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 26 publications
2
53
1
Order By: Relevance
“…Flag-IRAK1, Flag-IRAK4 and MyD88-Myc were kindly given by Professor Thomas Miethke (Technische Universität München, Germany) [28]. TRIF-HA was provided by Dr Luke AJ O'Neill (Trinity College Dublin, Ireland) [29] and Flag-TLR3 (Addgene plasmid 32712) was a gift of Saumen Sarkar (University of Pittsburgh Cancer Institute, USA) [30].…”
Section: Cell Culture and Plasmidsmentioning
confidence: 99%
“…Flag-IRAK1, Flag-IRAK4 and MyD88-Myc were kindly given by Professor Thomas Miethke (Technische Universität München, Germany) [28]. TRIF-HA was provided by Dr Luke AJ O'Neill (Trinity College Dublin, Ireland) [29] and Flag-TLR3 (Addgene plasmid 32712) was a gift of Saumen Sarkar (University of Pittsburgh Cancer Institute, USA) [30].…”
Section: Cell Culture and Plasmidsmentioning
confidence: 99%
“…In mammals, TMED10 can bind to the MHC class I heavy chain and may protect free MHC class I heavy chains from destruction by ER-associated degradation (26). TAG and TMED7, which contain GOLD domains, have been demonstrated to negatively regulate MyD88-independent TLR4 signaling by displacing the adaptor TRIF from TRAM in the TLR4 signaling complex (20,21). Given that TMED7 regulates TLR4 signaling and that TMED1 has been shown to potentially interact with ST2L, we sought to determine whether TMED1 is involved in the ST2L signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…TMED proteins are membrane-spanning proteins that were thought to have their N terminus and GOLD domain located in the ER/Golgi lumen and their C terminus on the cytosolic side of the membrane. However, recent data regarding TMED7 have demonstrated that it possesses an N-terminal transmembrane domain that is responsible for its ability to traverse the membrane and that its GOLD domain is actually located in the cytosolic compartment (20). Transmembrane prediction programs used to analyze the TMED1 sequence suggest that it does not possess a second transmembrane domain located at the N terminus, which corresponds to the region in which the transmembrane domain in TMED7 is found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations